DANGER RISKS DURING THE OPERATION OF INDUSTRIAL GAS PIPELINES - Kryvenko, G. М; Kryvenko, O. V.; Semchuk, Ya. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2024)
Ensuring the safety of pipeline transport of hydrocarbon energy carriers is one of the priority tasks in the oil and gas industry. Oil and gas pipelines are an integral part of technological schemes of oil and gas production facilities. Their total length coincides with the length of main pipelines. Therefore, special attention is paid to improving the safety of the operation of industrial pipelines. Safe functioning, operational analysis of the most dangerous limit states is a guarantee of the reliability of the operation of industrial pipelines. Man-made emergencies make the greatest contribution to the totality of emergency situations, therefore measures to respond, prevent and eliminate the consequences of man-made emergencies as the most widespread and threatening are necessary. The purpose of the work is to study the risks of danger during the operation of industrial pipelines. To achieve the goal, the following tasks were solved: forecasting the mass flow of gas in the event of a pipeline rupture and risk assessment. The object of the study is an industrial pipeline with a significant service life. The causes of failures in pipeline systems are welding defects, mechanical damage, internal corrosion, and others. The most damaging accidents on pipelines occur in the case of longitudinal pipe fractures, which can occur both on the main metal of the pipes and in the zone of welds when corrosion "fistulas" and "guillotine" tears are formed. Emergency gas releases can catch fire. .The nature of the change in the mass flow of gas during a pipeline rupture was determined depending on the diameter, initial pressure, time and distance from the place of damage to the pipline. Gas leakage during a pipeline rupture, which causes damage to the environment, depends on the diameter and length of the disconnected section. To ensure extended service life and safe operation of industrial pipelines with a significant service life, it is necessary to adjust the pressures at the beginning of the pipeline. During risk assessment, it is important to take into account indicators of the impact of individual technological processes on the occurrence of an emergency situation.